2021
DOI: 10.1016/j.chiabu.2021.105212
|View full text |Cite
|
Sign up to set email alerts
|

Abusive and positive parenting behavior in Japan during the COVID-19 pandemic under the state of emergency

Abstract: Background The Coronavirus Disease 2019 (COVID-19) pandemic has changed the lives of children and parents, raising concerns about child maltreatment. Objective We examined the prevalence of abusive parenting behavior during the pandemic of the COVID-19 and its relations with physical, psychological, and social factors and positive parenting behavior. Participants and setting An online survey was performed during the COVID-19 state of emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 39 publications
4
39
0
2
Order By: Relevance
“…For instance, school closures as a preventive action led to students struggling with unexpected disturbances in their daily routine. Low physical activity, anxiety and depression, fear of the uncertain future, poor interaction and parent-child conflicts, and increased sedentary behavior are all among the negative impacts of the COVID-19 pandemic on the mental health of children and consequently the family (6). According to this mental health crisis, the implementation of targeted intervention can be essential (5).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, school closures as a preventive action led to students struggling with unexpected disturbances in their daily routine. Low physical activity, anxiety and depression, fear of the uncertain future, poor interaction and parent-child conflicts, and increased sedentary behavior are all among the negative impacts of the COVID-19 pandemic on the mental health of children and consequently the family (6). According to this mental health crisis, the implementation of targeted intervention can be essential (5).…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, positive parenting might be considered an important protective and facilitating factor of parent and family resilience ( Walsh, 2004 ; Miller-Graff et al, 2020 ) in the pandemic context. In this line, Yamaoka et al (2021) found that positive parental behaviors, especially those showing empathy, were associated with a lower risk of abusive behavior during the pandemic. By contrast, abusive parent behaviors were associated with greater use of screens, mental health problems of mothers, and intrafamily violence.…”
Section: Introductionmentioning
confidence: 91%
“…The types of games given to children greatly affect the psychological condition of children which will affect them when they are adults, therefore it is necessary to pay attention to the types of games according to their age [17]. varied atmosphere [20].…”
Section: The Selection Of Educational Game Toolsmentioning
confidence: 99%